Implikasi Internalisasi Nilai Nilai Ajaran Islam Dalam Pembelajaran PAI Terhadap Kesadaran Moral Siswa - Raito, Raito; Sukmawati, Siska (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
This research is driven by observations of the low moral awareness among students. Evidence of this includes students violating rules, displaying a lack of discipline, attending and entering classes at their discretion rather than adhering to the set schedule, using coarse language, and lacking enthusiasm in their studies. The aim of this study is to describe the implications of internalizing Islamic values within Islamic Religious Education (PAI) lessons on students' moral awareness. The research employs a qualitative descriptive method. Data collection techniques include observation, interviews, and documentation. The data analysis involves data reduction, data presentation, and conclusion drawing. The results of this study indicate that internalizing Islamic values in the school environment and within PAI lessons positively impacts students' moral awareness. This is demonstrated by activities such as praying before starting lessons, performing congregational prayers, and engaging in practical applications and reflection on PAI learning materials.  Keywords: Internalization, Islamic Values, PAI Education, Moral Awareness